The Role of Ionic Liquids in Textile Processes: A Comprehensive Review - Anastasia Anceschi; Claudia Riccardi; Alessia Patrucco (Molecules)
Thanks to their unique physicochemical properties, ionic liquids (ILs) have moved from niche academic interest to critical components in various industrial applications. The textile industry, facing significant environmental and economic pressures, has begun to explore ILs as sustainable alternatives to traditional solvents and chemicals. This review summarizes research on the use of ILs in various textile processes, including dyeing, finishing, and fiber recycling, where their high thermal stability, tunable solubility, and low volatility are exploited to reduce resource consumption and environmental impact. The discussion also extends to the integration of ILs in textile waste recycling, highlighting innovative approaches to fiber dissolution and regeneration aimed at circular economy goals. Despite these advances, challenges such as high production costs and scalability remain barriers to the widespread adoption of ILs in the textile sector. Addressing these barriers through continued research and development is essential to fully realize the potential of ILs for sustainable transformation in textiles.